2022
DOI: 10.3390/genes13071227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Reference Genes for RT-qPCR Analysis in Gleditsia microphylla under Abiotic Stress and Hormone Treatment

Abstract: Gleditsia microphylla is an important galactomannan gums source plant with characteristics of drought resistance, barren tolerance, and good adaptability. However, the underlying molecular mechanisms of the biological process are not yet fully understood. Real-time quantitative PCR (RT-qPCR) is an accurate and convenient method to quantify the gene expression level and transcription abundance of suitable reference genes. This study aimed to screen the best internal reference genes in G. microphylla under abiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In addition, we compared the expression levels of AtACT2 (Arabidopsis) with those of ACT7 and the stable reference genes RPL27 and RPS15 (C. burmnnii) under the Nacl-treated samples (Figure S3), showing that the stability of At-ACT2 was relatively lower. Based on the previous research, TATA-box, as the first promoter found in eukaryotes, was more suitable for q−PCR analysis in a variety of species, such as in Monomorium pharaonic [1], Gleditsia microphylla [56] and Dendrobium huoshanense [57], but in our study it was not the optimum reference gene for some experimental conditions. In addition, eIF-5A was just the best reference gene in different borneol clones and EF1α was the optimum gene for studying different tissues.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, we compared the expression levels of AtACT2 (Arabidopsis) with those of ACT7 and the stable reference genes RPL27 and RPS15 (C. burmnnii) under the Nacl-treated samples (Figure S3), showing that the stability of At-ACT2 was relatively lower. Based on the previous research, TATA-box, as the first promoter found in eukaryotes, was more suitable for q−PCR analysis in a variety of species, such as in Monomorium pharaonic [1], Gleditsia microphylla [56] and Dendrobium huoshanense [57], but in our study it was not the optimum reference gene for some experimental conditions. In addition, eIF-5A was just the best reference gene in different borneol clones and EF1α was the optimum gene for studying different tissues.…”
Section: Discussionmentioning
confidence: 72%
“…Pairwise variations Vn / Vn + 1 between consecutively ranked normalization factors are calculated GeNorm analysis to determine the optimal number of required reference genes. V value is lower than 1.5 indicated that n is the suitable reference gene number for accurate standardization (Yang et al, 2022). As shown in Figure 3, in the experimental condition of different tissues and developmental stages, dimethoate treatment, the values V 3/4 were less than 0.15, indicating that three reference genes were sufficient for reliable standardization, while under the condition of different genders or the treatment of different feeding densities, the values V 2/3 were less than 0.15, and thus two reference genes should be selected.…”
Section: Resultsmentioning
confidence: 99%
“…Primers were screened by PCR and agarose gel electrophoresis. The primers with clear bands, good specificity and no primer dimer were selected for further qRT-PCR assay ( Yang et al., 2022 ). The final primer with a single peak melting curve should be selected ( Feng et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the stability of reference genes were different in various growth environment and growth period. The expression levels of TBP1 and EIF4A1 were the most stable reference genes in Gleditsia microphylla under cold, hot and dry growth conditions and hormone treatment ( Yang et al., 2022 ). elF-4α and ACT1 were the most stable internal reference genes at different developmental stages of rice seeds ( Li et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%